A Review of the Neurosurgical Management of Brain Metastases During Pregnancy. (20th September 2021) - Proskynitopoulos, Phileas J.; Lam, Fred C.; Sharma, Sunjay; Young, Brett C.; Laviv, Yosef; Kasper, Ekkehard M.
Abstract: Objective: Patients with pregnancy-associated secondary brain tumors (PASBT) are challenging to manage. Because no guidelines for the management of such patients currently exist, we performed a systematic review of the literature using PRISMA guidelines with a discussion of management from a neurosurgeon's perspective. Method: Systematic review of the literature using PRISMA guidelines from 1999 to 2018. Results: We identified 301 studies of which 16 publications (22 patients reporting 25 pregnancies, 20 deliveries, 5 early terminations) were suitable for final analysis. The most frequent primary cancers were breast (8/22, 36.36%), skin (6/22, 27.27%), and lung (5/22, 22.73%). Four patients (18.18%) had neurosurgical procedures during their pregnancies. Five patients (22.73%) received neurosurgical resection after their pregnancies. Nine patients (40.91%) received radiation therapy and seven patients (31.82%) received chemotherapy during pregnancy while seven patients (31.82%) received chemotherapy and radiation after pregnancy. There was 1 fetal death (5%) out of 20 healthy deliveries. Five pregnancies (20%) were terminated in the first trimester due to a need for urgent neurosurgical intervention. Conclusion: Management of PASBT remains a challenging issue. Maternal and fetal risks associated with surgical resection and teratogenicity due to adjuvant therapy should be discussed in the context of a multidisciplinary team. Timing of surgery and the use of systemic chemoradiation depends on the gestational age (GA) of the fetus, extent, and control of the mother's primary and metastatic disease. Guidelines need to be established to help neuro-oncology teams safely and effectively manage this group of patients.